2007
DOI: 10.1182/blood-2006-11-060087
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between B7-H1 and PD-1 determines initiation and reversal of T-cell anergy

Abstract: IntroductionInteraction of receptors and ligands between T cells and antigenpresenting cells (APCs) is a very early event for transmitting signals to control T-cell growth, differentiation, tolerance, and death. 1 For example, cytotoxic T lymphocyte (CTL)-associated antigen 4 (CTLA-4), which is rapidly up-regulated on activated T cells and delivers an inhibitory signal to T cells upon binding to CD80/CD86, antagonizes CD28 costimulation and maintains T-cell homeostasis and selftolerance. 2 CTLA-4 signaling, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
181
4
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(199 citation statements)
references
References 27 publications
10
181
4
3
Order By: Relevance
“…These observations strikingly resemble the early events in FV infection, which is represented by the rapid expansion of virus-infected, PD-L1 Hi erythroblasts and rapid exhaustion of CD8 + T cells, although the severity of virus infection and CD8 + T cell exhaustion between these models differs in degree. Considering that CD8 + T cells upregulate inhibitory molecules at very early stages under the tolerogenic environment and that the negative signals provided at this stage have a profound impact on the early fate-decision of CD8 + T cells (44,58), prevention of the potential negative signals during the priming/differentiation phase is rational for rescuing virus-specific CD8 + T cells from terminal exhaustion and for the effective elimination of virus-infected cells, as we successfully demonstrated in the current study.…”
Section: Discussionmentioning
confidence: 74%
“…These observations strikingly resemble the early events in FV infection, which is represented by the rapid expansion of virus-infected, PD-L1 Hi erythroblasts and rapid exhaustion of CD8 + T cells, although the severity of virus infection and CD8 + T cell exhaustion between these models differs in degree. Considering that CD8 + T cells upregulate inhibitory molecules at very early stages under the tolerogenic environment and that the negative signals provided at this stage have a profound impact on the early fate-decision of CD8 + T cells (44,58), prevention of the potential negative signals during the priming/differentiation phase is rational for rescuing virus-specific CD8 + T cells from terminal exhaustion and for the effective elimination of virus-infected cells, as we successfully demonstrated in the current study.…”
Section: Discussionmentioning
confidence: 74%
“…In conventional T cells, PD-1 is not expressed on naive T cells, but it is inducibly expressed after T cell activation (36). In recent reports, PD-1 and its ligands have been implicated in the induction and maintenance of T cell and NKT cell anergy (37,38,42,43). In our previous report, we demonstrated that NKT cell dysfunction was associated with upregulation of inhibitory receptor PD-1 in active tuberculosis, and it was partially recovered by blockade of PD-1 (44).…”
Section: Discussionmentioning
confidence: 99%
“…Blockade of PD-L1 also accelerated GVHD disease lethality in irradiated bone marrow recipients (35). PD-1/PD-L1 appeared also to be responsible for the induction and the maintenance of T cell unresponsiveness in an in vivo model of functional anergy in TCRtransgenic T cells induced by high doses of antigenic peptide (36). The other prototype of CD28 family inhibitory receptors is CTLA-4 (CD152) (37).…”
Section: Figurementioning
confidence: 99%